Evolution of robotic-assisted kidney transplant: successes and barriers to overcome. Issue 1 (January 2021) - Matthew, Ashley N.; Hampton, Lance J.; Autorino, Riccardo; Bhati, Chandra S.
Abstract : Purpose of review: The aim of this study was to provide an updated review of robotic-assisted kidney transplant (RAKT) with an emphasis on advantages over the open kidney transplant (OKT), utility in special populations and resources available to overcome the learning curve of robotic surgery. Recent findings: The majority of the reported studies showed that RAKT and OKT have similar functional outcomes including similar ischemia times and time to postoperative normalization of creatinine. However, RAKT results in fewer wound complications, decreased estimated blood loss and pain. Given these benefits, RAKT is a promising approach for obese patient across BMI subtypes and several studies showed decreased wound complications in this population compared with the open approach. Moreover, new 3D-print techniques are promising resources for robotic simulation, which may decrease the learning curve of robotic surgery. Summary: Overall, RAKT is a feasible approach especially in obese patients. However, more data with long-term follow-up are needed to fully elucidate the advantages over OKT before universal implementation of this approach is possible.